SDZ MRL 953, A Novel Synthetic Lipid a Analogue, Induces Tolerance to the Lethal Effects of Endotoxin and Enhances Nonspecific Immunity - Charles Lam; Eberhard Schütze; Emmanuel Quakyi; Ekke Liehl; Peter Stütz (Canadian Journal of Infectious Diseases)
Despite the availability of potent antimicrobials, shock due to Gram-negative rod sepsis remains an important clinical concern in immunosuppressed patients. Current strategies for treating septic shock by removal of endotoxin (lipopolysaccharides [LPS]) or putative mediators have only been partially effective. An attractive alternative appears to be the induction of hyporesponsiveness to LPS by synthetic lipid A analogues. SDZ MRL 953, a novel prototype of lipid A analogues. was examined for its ability to induce early-phase tolerance against experimental endotoxemia in mice following single or multiple administrations 2, 24, or 72 h before challenge. The analogue protected mice against a lethal dose of LPS or infections in a time- and dose-dependent manner. Maximum effects were observed in animals pretreated with SDZ MRL 953 on three consecutive days before the LPS challenge or microbial inoculation. To examine the mechanisms involved, peritoneal macrophages from the tolerant mice were monitored ex v1vo for the release of tumour necrosis factor (TNF) and killing of an isolate of Escherichia coli. It was found that macrophages from endotoxin-tolerant mice produced only a fraction of the TNF released by cells from control groups in response to LPS. However, the killing of E coli by the macrophages was enhanced. In conclusion, SDZ MRL 953 may have a prophylactic potential in reducing the risk of endotoxic shock in traumatized or in myelosuppressed patients.